HUBUNGAN KARAKTERISTIK SUAMI DENGAN KEIKUTSERTAAN SUAMI MENJADI AKSEPTOR KELUARGA BERENCANA DI WILAYAH DESA KARANGDUWUR KECAMATAN PETANAHAN KABUPATEN KEBUMEN JAWA TENGAH - Maharyani, Hesti Wahyu; Handayani, Sri (Universitas Ahmad Dahlan, 2010)
Background : Family planning program is a program intended to help couples and individualsachieve their reproductive goals. The low participation of men in family planning can have negativeimpact on womens reproductive health because of not only women are always actively involved, sowomen emancipation who demanded equality of rights between men and women becomes a reality.The purpose of this study is to determine the relationship between the characteristics of the husbandwith the participation of husbands become acceptors of family planning in the Village areaKarangduwur Petanahan Kebumen district of Central Java.Methods : This was a observasional analytic research using cross sectional research design in thisstudy were all husbands of childbearing age (EFA) in the Village Karangduwur Petanahan Kebumendistrict of Central Java. The number of samples taken in this study is 85 people. Data analysis wasperformed univariate and bivariate.Result : Result of hypothesis test showed that husband characteristic in terms of revenue associatedwith the participation of husbands in family planning as indicated by the value of Chi Square = 7.743(p = 0.005 <0.05), husband characteristic in terms of knowledge is not related to the participation ofhusbands in family planning as indicated by the value Chi Square = 0.022 (p = 0.882> 0.05), characteristic husband in terms of education is not related to the participation of husbands in family planning as indicated by the value of Chi Square = 2.292 (p = 0.130> 0.05), husband characteristic in terms of number of children associated with the participation of husbands in family planning as indicated by the value of Chi Square = 10.916 (p = 0.01<0,05). Conclusion : From four independent variables studied there was a significant correlation factors there are income, and number of children, or parity, and there was no significant correlation: education and knowledge. Keywords : Husband Participation, Family Planning Program, Acceptor.